Dimensional Taxonomy of Data Visualization: A Proposal From Communication Sciences Tackling Complexity - Cavaller, Victor (Frontiers in Research Metrics and Analytics, 2021)
This article consists of a conceptual analysis - from the perspective of communication sciences - of the relevant aspects that should be considered during operational steps in data visualization. The analysis is performed taking as a reference the components that integrate the communication framework theory - the message, the form, the encoder, the context, the channel and the decoder – which correspond to six elements in the context of data visualization: content, graphic representation, encoding set-up, graphic design and approach, media, and user. The study is focused accordingly on the dimensions that these elements describe: the degrees of abstraction of the information; the functionalities of the tool for the graphical representation, the specifications for the set-up of the visualization, the approach modes to the context by the graphic design, the levels of communication efficiency in the media and the requirements of the visualization perceived as values from the user experience side. The unfolding of these dimensions is undertaken following a common pattern of six organizational layers of complexity - basic, extended, synthetic, dynamic, interactive and integrative – according to analytical criteria. The results of the detailed study, based on an extensive scientific literature review, allow the design of a dimensional taxonomy of data visualization built on a matrix structure where these elements act as factors of completeness and the layers act as factors of complexity. As a conclusion, an object-centred model constituted by an ordered series of phases and achievements is proposed as a guide to complete a systematic process of data visualization.